Optical Modulator Using Channel Optical Waveguides and Planar Patch-Antennas with Gaps - Yusuf Nur Wijayanto; Hiroshi Murata; Yasuyuki Okamura (Jurnal Elektronika dan Telekomunikasi, 2015)
Optical modulator using channel optical waveguides and planar patch-antennas with gaps on ferroelectric optical crystals were proposed. Basic operations for receiving a wireless microwave signal and directly converting it to a lightwave signal were demonstrated successfully using a prototype device with simple and compact structure. These devices operate with no external power supply and no additional modulation electrode. Therefore the microwave-lightwave conversion with low microwave distortion can be obtained. The advanced microwave-lightwave converters using patch-antennas with a pair of narrow gaps and their applications are also discussed